Analisis Minat Meyimpan Dana Pada Bank Syariah Di Kalangan Mahasiswa Menggunakan Alat Bantu SPSS (Studi kasus: Mahasiswa Universitas Islam Negeri Sumatera Utara) - Akbar Nugraha; Dwi Gustantia; Chairina Chairina (AGHNIYA : Jurnal Ekonomi Islam, 2022)
This study was made based on the results of previous mini research, aims to determine Universitas Islam Negeri Sumatera Utara college students in  Medan interest of saving Islamic bank in Medan. This research is descriptive quantitative research using primary data. The variables used in this research consisted of a bank's reputation, confidence, and location as the independent variable and the interest of saving the student as the dependent variable. Sampling technique is done by interview35 college students of Universitas Islam Negeri Sumatera Utara in Medan as a sample. The Methods of data collection use a self administrated survey, by giving questionnaires. The method used in this research is the descriptive statistical analysis with SPSS software. Based on the results of analysis, it was found that Universitas Islam Negeri Sumatera Utara college students' interest in saving in Islamic banks in Medan is still low. Based on the data obtained it is known that bank reputation variables, beliefs, and location affect student interest in the Universitas Islam Negeri Sumatera Utara decided to save the Islamic bank in Medan. The main obstacle that affects Universitas Islam Negeri Sumatera Utara college students' interest to save their money in Islamic banks is the location away from home.